Citicoline: A Food Beneficial for Patients Suffering from or Threated with Glaucoma - Grieb, Pawel; Jünemann, Anselm; Rekas, Marek; Rejdak, Robert (Frontiers in Aging Neuroscience, 2016)
Oral form of citicoline, a nootropic and neuroprotective drug in use for almost five decades, recently was pronounced a food supplement in both USA and EU. The idea of adding citicoline to topical treatment of primary open angle glaucoma (POAG) aimed at decreasing intraocular pressure (IOP) appeared as a logical consequence of accepting neurodegenerative character of this disease. Experimental data, and also few clinical studies indicate that this substance has potential to counteract some important pathological mechanisms which seem to contribute to POAG initiation and progression, such as excitotoxicity and oxidative stress.